Técnicas de navegación y turismo fluvial en el río Babahoyo Provincia de Los Ríos - Jaime Lamilla, Mirka Itati (2019)
The Babahoyo canton has different tourist attractions that have scenic beauty and historical value which must be shared to increase the tourist development of the canton, this research aims to promote the valorization of river tourism activities for this purpose different methodologies will be applied that will contribute to the realization of the objectives, for this purpose, a lifetime was based on one of the objectives of the national plan that manifests the guarantee of plural participation with a gender focus on peoples, nationalities, commune, communities and collective in the management of resources Natural and environmental services. This motivates the communities to carry out activities that promote the preservation of the natural resources they have in order to be productive, responsible and generate income to their homes. It is in this way that the valorization of activities that were carried out years ago and transmitted from generation to generation until today without losing its essence is achieved